2016
DOI: 10.1055/s-0042-112367
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Induces a Moderate Steatohepatitis Accompanied by Liver Regeneration, Mast Cells Infiltration, and Changes in the Expression of the Farnesoid X Receptor

Abstract: Hypothyroidism is associated with the development of non-alcoholic steatohepatitis, but cellular mechanisms have been scarcely analyzed. Thyroid hormones regulate the synthesis and secretion of bile acids that are endogenous ligands of the farnesoid receptor (FXRα), which have been involved in the development of non-alcoholic steatohepatitis. However, the relationship between thyroid hormones and FXRα expression in the liver is yet unknown. Control (=6) and methimazole-induced hypothyroid (=6) female rabbits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…There are miscellaneous reports in conformity with our findings, which show lipid depositions in drug-induced hypothyroid models (22,23), whereas there are also some in contrast (24,25). Our histological studies indicated the accumulation of glycogen depositions in the liver of the hypothyroid group as suggested by others (26).…”
Section: Discussionsupporting
confidence: 92%
“…There are miscellaneous reports in conformity with our findings, which show lipid depositions in drug-induced hypothyroid models (22,23), whereas there are also some in contrast (24,25). Our histological studies indicated the accumulation of glycogen depositions in the liver of the hypothyroid group as suggested by others (26).…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, adipocytes from the VAT of diverse mammals express TRs and deiodinases, suggesting a direct effect of thyroid hormones on this tissue [48]. Additionally, dyslipidemias and hypertrophy of the periovarian VAT found in hypothyroid virgin rabbits seems to be accompanied by steatohepatitis [49]. This conjunction of results could help to explain the link between ovarian dysfunction and nonalcoholic fatty liver disease, obesity, insulin resistance, and dyslipidemias observed in women [50].…”
Section: Discussionmentioning
confidence: 99%
“…MB07811 treatment reduced liver steatosis and lowered plasma free fatty acid, triglyceride, and serum AST while upregulating lipid metabolism genes [42]. Finally, similar phenotypes were also noted in rabbits, where hypothyroidism induced moderate NASH [43].…”
Section: Linking Thyroid Hormone and Its Receptors To Chronic Liver Dmentioning
confidence: 58%